MicroRNAs regulate granulosa cells apoptosis and follicular development — A review - Zhuandi Gong; Juan Yang; Shengju Bai; Suocheng Wei (Asian-Australasian Journal of Animal Sciences, 2020)
Objective MicroRNAs (miRNAs) are the most abundant small RNAs. Approximately 2,000 annotated miRNAs genes have been found to be differentially expressed in ovarian follicles during the follicular development (FD). Many miRNAs exert their regulatory effects on the apoptosis of follicular granulosa cells (FGCs) and FD. However, accurate roles and mechanism of miRNAs regulating apoptosis of FGCs remain undetermined. Methods In this review, we summarized the regulatory role of each miRNA or miRNA cluster on FGCs apoptosis and FD on the bases of 41 academic articles retrieved from PubMed and web of science and other databases. Results Total of 30 miRNAs and 4 miRNAs clusters in 41 articles were reviewed and summarized in the present article. Twenty nine documents indicated explicitly that 24 miRNAs and miRNAs clusters in 29 articles promoted or induced FGCs apoptosis through their distinctive target genes. The remaining 10 miRNAs and miRNAs of 12 articles inhibited FGCs apoptosis. MiRNAs exerted modulation actions by at least 77 signal pathways during FGCs apoptosis and FD. Conclusion We concluded that miRNAs or miRNAs clusters could modulate the apoptosis of GCs (including follicular GCs, mural GCs and cumulus cells) by targeting their specific genes. A great majority of miRNAs show a promoting role on apoptosis of FGCs in mammals. But the accurate mechanism of miRNAs and miRNA clusters has not been well understood. It is necessary to ascertain clearly the role and mechanism of each miRNA or miRNA cluster in the future. Understanding precise functions and mechanisms of miRNAs in FGCs apoptosis and FD will be beneficial in developing new diagnostic and treatment strategies for treating infertility and ovarian diseases in humans and animals.